Progress Through Engagement: A Systematic Review and Thematic Synthesis of Qualitative Community‐Based Participatory Research in Vision Impairment. - Tavoulari, Aikaterini; Kidwai, Jibraan; Proulx, Michael J.; Petrini, Karin (Health Expectations, 2026)
Background: Vision impairment (VI) presents complex challenges that extend beyond clinical measures, affecting individuals' mental health, social participation and quality of life. Traditional research often overlooks these lived realities, prompting a growing interest in community‐based participatory research (CBPR) as a more inclusive and impactful approach. Methods: This systematic review examines the scope, frequency and methodological characteristics of CBPR studies involving people with VI, with a focus on qualitative research published between 1993 and 2024. Following PRISMA guidelines and PROSPERO registration, included studies were identified across diverse cultural contexts and participatory depths, from consultation to collaboration and user‐driven design. Using a dual‐stage thematic synthesis, we explored both the methodological approaches ('how') and the substantive content themes ('what') addressed in these studies. Participatory methods included photography and narrative storytelling, focus groups, creative workshops and final consultations, with many studies employing methodological triangulation. Although the search covered the period 1993–2024, all included studies were published between 2014 and 2024, reflecting the recent emergence of CBPR approaches in VI research. Results: Twelve studies met the inclusion criteria and were included in the final synthesis. Thematic findings revealed barriers to accessibility, cultural misalignment in interventions and the importance of user‐led adaptation strategies, showing that despite growing interest, CBPR remains underutilised in VI research. Conclusion: This review highlights its potential to bridge gaps between clinical innovation and lived experience, offering a roadmap for more equitable, context‐sensitive and user‐centred research practices. Patient or Public Contribution: Patients and members of the public were not directly involved in the design, conduct, or analysis of this systematic literature review. Instead, the study focus and synthesis were informed by documented experiences of people with vision impairment, derived from community‐based participatory studies, which contributed to the development of patient‐centred health material design.